2012
DOI: 10.14310/horm.2002.1362
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroids and personality traits in the middle luteal phase of healthy normally menstruating young professional women

Abstract: .10, F(1,57)=6.23, p=0.016). We were unable to find any association between the circulating androgens and scores on the masculinity-femininity scale (Mf). We were also unable to document any association between the weak adrenal androgens DHEA and DHEA-S and depression in contrast to several published reports. (c) Our data suggest a marginally significant association between progesterone and scores on the 7-Pt (obsessive/compulsive/psychasthenia) scale (r=0.27, p<0.05). However, only 7% of the 7-Pt variance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…It has been suggested that disgust is closely related to several anxiety disorders, including contamination-related OCD (Cisler, Olatunji, & Lohr, 2009;Olatunji, Unoka, Beran, David, & Armstrong, 2009). Another study showed a significant positive correlation between progesterone and scores on the Psychastenia (obsessivecompulsive symptoms) scale in the Minnesota Multiphasic Personality Inventory (Avgoustinaki et al, 2012). During the luteal phase women were also more likely to express behaviors such as cleaning (Dillon, 1992) or obsessive pulling of hair considered an overexpression of the prophylactic behavior of grooming (Keuthen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that disgust is closely related to several anxiety disorders, including contamination-related OCD (Cisler, Olatunji, & Lohr, 2009;Olatunji, Unoka, Beran, David, & Armstrong, 2009). Another study showed a significant positive correlation between progesterone and scores on the Psychastenia (obsessivecompulsive symptoms) scale in the Minnesota Multiphasic Personality Inventory (Avgoustinaki et al, 2012). During the luteal phase women were also more likely to express behaviors such as cleaning (Dillon, 1992) or obsessive pulling of hair considered an overexpression of the prophylactic behavior of grooming (Keuthen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogen disgust may reduce risks of contact with an infection by generating intense negative feeling against potential sources of infection (Curtis, Aunger, & Rabie, 2004;Curtis & Biran, 2001;Fessler & Navarrete, 2003). Other studies in the CPH area investigated preferences for healthy faces (Jones et al, 2005), hygiene concerns (Fleischman & Fessler, 2011;Zelazniewicz et al, 2016), or intensification of obsessive-compulsive disorders' (OCD) symptoms (Avgoustinaki et al, 2012;Keuthen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally high levels of progesterone in the midluteal compared to the early follicular phase have been related to heightened amygdala activity to negative stimuli (Andreano & Cahill, 2010), and exogenous progesterone administration increased negative mood in women that were in the early follicular phase (Klatzkin et al, 2006). Furthermore, progesterone administration has been shown to increase amygdala reactivity to angry and fearful faces (Van Wingen et al, 2008), and greater levels of progesterone have been associated with increased self-reported proneness to anxiety in the form of excessive doubts, compulsions, obsessions, and unreasonable fears (Avgoustinaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In adolescent females higher free and bioavailable testosterone has been linked to aggressiveness (Pajer et al, 2006). Total testosterone in women has in one study been found to correlate with paranoia traits on the Minnesota Multiphasic personality inventory (Avgoustinaki et al, 2012).…”
Section: Cognition and Personalitymentioning
confidence: 95%